2018
DOI: 10.1530/rep-17-0667
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid synthesis and role in uterine epithelia proliferation

Abstract: Sphingolipids are involved in the regulation of cell proliferation. It has been reported that diacylglycerol and sphingosine-1-phosphate generation, during the synthesis of phospho-sphingolipids, is necessary for both, G1-S transition of cell cycle during the sustained activation of protein kinase C in various cell models (MDCK, and) and AKT pathway activation. During the estrous cycle of the rat, AKT signaling is the main pathway involved in the regulation of uterine cell proliferation. The aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
1
4
0
1
Order By: Relevance
“…The conflicting data might be due to the species or experimental processing time. Similar to our result, many research results found that the LPC decreased in HFD mice , and obese humans. , In addition, it has been demonstrated that SM synthesis increased during proliferation of uterine cells in the estrous cycle of the rat . Furthermore, endometrial PE increased late in the oestrous cycle in the ewe, and the concentrations of the SM, phospholipids, and LPC increased at different stages of the estrous cycle of bovine .…”
Section: Discussionsupporting
confidence: 91%
“…The conflicting data might be due to the species or experimental processing time. Similar to our result, many research results found that the LPC decreased in HFD mice , and obese humans. , In addition, it has been demonstrated that SM synthesis increased during proliferation of uterine cells in the estrous cycle of the rat . Furthermore, endometrial PE increased late in the oestrous cycle in the ewe, and the concentrations of the SM, phospholipids, and LPC increased at different stages of the estrous cycle of bovine .…”
Section: Discussionsupporting
confidence: 91%
“…Several SPL metabolites, especially ceramide (Cer) and sphingomyelin (SM), act as key bioactive molecules to control critical cellular functions, such as cell cycle, aging, apoptosis, cell migration, and inflammation (Hannun and Obeid 2008). Cerbón et al (2018) reported that, myriocin, an inhibitor of sphingolipid synthesis, is used during estrus, before the start of the new cell cycle in epithelial cells. The results showed that the abundance of sphingomyelin was reduced, accompanied by the stagnation of the proliferation of uterine epithelial cells on metestrus day.…”
Section: Discussionmentioning
confidence: 99%
“…However, p21 was also known to be regulated by p53-independent signaling pathway [ 35 , 36 ]. During the synthesis of phospho-sphingolipids, the generation of diacylglycerol and sphingosine-1-phosphate is necessary for the G1-S transition of cell cycle [ 37 ]. Sphingolipid pathway-mediated the activation of the NF-κB [ 38 ].…”
Section: Discussionmentioning
confidence: 99%